Pengaruh Dukungan Organisasi, dan Budaya Organisasi Melalui Komitmen Organisasi sebagai Variabel Mediasi terhadap OCB (Organizational Citizenship Behaviour) (Suatu Kajian Studi Literatur Manajemen Sumberdaya Manusia) - Minda Suharti Lubalu, Beby; EHJ FoEh, John; Sia Niha, Simon (Dinasti Review Publisher, 2023)
This scientific work describes the literature review that influences OCB (organizational citizenship behavior), namely organizational commitment as an intervening variable, as well as organizational support and organizational culture. Writing this scientific paper intends to make hypotheses that influence between variables so that writing other works can use them as a reference. The results obtained consist of organizational support having a positive and important impact on organizational commitment; organizational culture has a positive and important impact on organizational commitment; support has a positive and important impact on OCB (organizational citizenship behavior); organizational culture has a positive and important effect on OCB (organizational citizenship behavior); organizational commitment has a positive and important impact on OCB; organizational commitment can mediate organizational support that influences OCB; organizational commitment can mediate organizational culture which results in OCB; organizational support or organizational culture simultaneously has a positive and important impact on OCB.